Orchestration: an instrument for implementing the Sustainable Development Goals - Stephan Klingebiel; Sebastian Paulo (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
From 25 to 27 September 2015, governments will meet at the United Nations (UN) in New York to adopt the Sustainable Development Goals (SDGs). As the list of 17 goals is now on the table, attention is shifting to the next phase of the new framework for global development: implementation. The UN Conference on Financing for Development in Addis Ababa in July 2015 has already laid some groundwork, but challenges remain. One major challenge will be to meet the growing demand for cooperation arising from the transformative and universal nature of the SDGs. The economic, social and environmental sustainability goals will not be limited to developing countries but apply to all countries in the world. In addition to national and local implementation, international cooperation must play a far-reaching role. This is especially true for goals such as a stable climate, sustainable consumption and production patterns, global health and security that can only be achieved through coordinated cross-border or global action. At the same time, the conditions for global collective action have changed substantially. The international system is now more multipolar due to the rise of emerging powers. Important multilateral processes are stalled or advance only slowly. In contrast, transnational networks have become a central feature of global governance and allow actors from civil society, the private sector, ministries, agencies, cities and municipalities to assume a global role. Successful examples such as the C40 Cities, the Extractive Industries Transparency Initiative and the Global Vaccine Alliance (Gavi) demonstrate that such networks can make important contributions to global sustainable development. These networks do not always emerge on their own and must overcome obstacles to cooperation. In various areas of sustainable development, such as environmental, health and development policy, approaches to foster global networks already exist under the catchword orchestration. Yet these efforts are still very piecemeal. Governments and international organisations should develop orchestration more systematically into an integral part of the instruments used to achieve the SDGs. An orchestration instrument for the SDGs would initiate, support and shape global networks. In addition, the instrument could specifically promote networks that integrate actors from middle-income countries into new cooperation initiatives for global public goods. The instrument would have two different objectives: firstly, mobilising contributions to global sustainable development (financing, sharing and co-creation of knowledge, standard setting, etc.) and, secondly, improving conditions for international cooperation as a whole (e.g. by reducing fragmentation or improving linkages between domestic and global policy processes). Government departments and international organisations from different policy areas could have a role in managing orchestration for the SDGs. In principle, development cooperation actors are in a position to play a leading role in getting such an instrument up and running. They have a number of relevant assets on which they can draw as orchestrators (financial resources, operational capacity, etc.). The orchestration of global networks might, however, stretch the existing limits of bi- and multilateral development cooperation (e.g. eligibility for official development assistance, the need to use certain implementation mechanisms).
Keywords: 330; Regionale + globale + transnationale Governance; Agenda 2030